HBR at 100 : the most influential and innovative articles from Harvard Business Review's first century. (Boston, Massachusetts : Harvard Business Review Press, 2022)
"Harvard Business Review is the foremost destination for smart management thinking. Now, at its 100th anniversary, this commemorative volume brings together the most influential ideas since its inception. With thought leaders including Michael E. Porter, W. Chan Kim and Renee Mauborgne, Rosabeth Moss Kantor, Peter Drucker, and Clayton M. Christensen, this book puts HBR's greatest concepts at your fingertips. HBR at 100 curates twenty of HBR's bestselling articles of all time on key topics such as leadership, strategy, innovation, entrepreneurship, and more. With an introduction by Harvard Business Review Editor-in-Chief Adi Ignatius and additional bonus content, you'll learn how these groundbreaking ideas continue to be relevant in today's business context-and what to keep in mind as you prepare for the future. Whether you're a longtime reader or you're picking up an HBR volume for the first time, this book offers all you need to understand the most critical ideas in management-and set yourself and your organization up for success"--
Managing Oneself / by Peter F. Drucker -- What Makes a Leader? / by Daniel Goleman -- Lead with Authenticity : An interview with Tina Opie / by Amy Bernstein, Sarah Green Carmichael, and Nicole Torres -- How Competitive Forces Shape Strategy / by Michael E. Porter -- Blue Ocean Strategy / by W. Chan Kim and Renée Mauborgne -- Disruptive Technologies: Catching the Wave / by Joseph L. Bower and Clayton M. Christensen -- Leading Change: Why Transformation Efforts Fail / by John P. Kotter -- One More Time: How Do You Motivate Employees? / by Frederick Herzberg -- The Power of Small Wins / by Teresa M. Amabile and Steven J. Kramer -- Why You Should Have (at Least) Two Careers / by Kabir Sehgal -- Becoming the Boss / by Linda A. Hill -- The Memo Every Woman Keeps in Her Desk / by Kathleen Reardon -- Why Do So Many Incompetent Men Become Leaders? / by Tomas Chamorro-Premuzic -- HBR at 100 : How to Promote Racial Equity in the Workplace / by Robert Livingston -- Harnessing the Science of Persuasion / by Robert B. Cialdini -- Barriers and Gateways to Communication / by Carl R. Rogers and F. J. Roethlisberger -- The Business of Artificial Intelligence / by Erik Brynjolfsson and Andrew McAfee -- Data Scientist: The Sexiest Job of the 21st Century / by Thomas H. Davenport and D.J. Patil -- Nine Things Successful People Do Differently / by Heidi Grant -- Management Time: Who's Got the Monkey? / by William Oncken, Jr., and Donald L. Wass -- Why the Lean Start-Up Changes Everything / by Steve Blank -- Bring Agile to the Whole Organization / by Jeff Gothelf -- The Three Types of Leaders of Innovative Companies : An interview with Deborah Ancona and Kate Isaacs / by Curt Nickisch -- Is Your Company Ready for a Zero-Carbon Future? / by Nigel Topping -- Design Thinking / by Tim Brown -- Marketing Myopia / by Theodore Levitt -- The Commercial Space Age Is Here / by Matt Weinzie
Includes index.
Description based upon online resource; title from PDF title page (viewed June 14, 2022).
Added to collection customer.56279.3
Keywords: Success in business; Industrial management; Succès dans les affaires; Gestion d'entreprise.; Industrial management; Success in business; elektronické knihy; electronic books